Coefficient of Algebraic Relationship Between Linear Dimensions as Growth Deduction for Rainbow Sardine Dussumieria Acuta in the Bay of Bengal - Ahmed, Zoarder Faruque; Fatema, Mst Kaniz; Zohora, Umme Habiba Az; Joba, Mansura Akter; Ahamed, Ferdous (Research in Agriculture Livestock and Fisheries, 2020)
The intercept as the coefficient of algebraic relationship between standard length (SL) and total length (TL), the two predominantly used linear dimensions of fin fish species, was referred to growth pattern deduction for rainbow sardine Dussumieriaacuta population in the Bay of Bengal. Monthly rainbow sardine samples were collected from the industrial fishing vessel in the Bay of Bengal over a period of a calendar year. The length-length relationship was formed algebraically as y=a+ bx. Linear relationship between SL and TL for male, female and unsexed populations was constructed separately. Chi-squared test affirmed that sex ratio between male and female did not deviate from the parity (P>0.05). The SL and TL ranges of male were 13.1-16.8and 16.4-20.7 cm respectively, they for female were13.4-17.2 and 16.5-20.9 cm respectively. Slope and intercept showed variation monthly in all length-length relationships regardless of sexes. The generalized SL-TL relationships of male, female and unsexed populations employing pooled data over the study period were TL=1.130SL+1.571 (R=0.908), TL=1.106SL+1.925 (R=0.911), and TL=1.114SL+1.825 (R=0.908) respectively. The correlation coefficients of all monthly and generalized regression analyses of all sex categories were very high (R≥0.786), a fact that explained the associations between two length dimensions were strongly related. Study revealed isometric growth for male in all months, while algometry was apparent for female and unsexed populations in a few months. Present findings of length-length relationship and growth pattern for D. acuta population in the Bay of Bengal would remain useful for future references. Res. Agric., Livest. Fish.7(3): 545-551, December 2020